2019
DOI: 10.3390/nu11112783
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein Consumption and the Risk of Type 2 Diabetes: ADose-Response Meta-Analysis of Prospective Studies

Abstract: The relationship between dietary protein consumption and the risk of type 2 diabetes (T2D) has been inconsistent. The aim of this meta-analysis was to explore the relations between dietary protein consumption and the risk of T2D. We conducted systematic retrieval of prospective studies in PubMed, Embase, and Web of Science. Summary relative risks were compiled with a fixed effects model or a random effects model, and a restricted cubic spline regression model and generalized least squares analysis were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 99 publications
6
56
0
3
Order By: Relevance
“…On the other hand, decreased consumption of red meat, fast food, as well as snacks (both salty and sweet) was also reported. White meat and dairy products are beneficial foods which contribute to the prevention of T2DM [ 19 , 20 ]. Increased consumption of fruits and vegetables is associated with a reduced risk of T2DM not only because they contain dietary fibre, essential vitamins and minerals, but also due to the antioxidant and anti-inflammatory effects of their components which include vitamins B and C, carotenoids, and polyphenols [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, decreased consumption of red meat, fast food, as well as snacks (both salty and sweet) was also reported. White meat and dairy products are beneficial foods which contribute to the prevention of T2DM [ 19 , 20 ]. Increased consumption of fruits and vegetables is associated with a reduced risk of T2DM not only because they contain dietary fibre, essential vitamins and minerals, but also due to the antioxidant and anti-inflammatory effects of their components which include vitamins B and C, carotenoids, and polyphenols [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several randomised controlled trials have demonstrated that increased dietary protein intake or whey protein (one of the two proteins in milk) supplementation increase circulating IGF-1 levels [ 45 47 ]. Intake of protein, particularly from animal sources, has been found to be positively associated with type 2 diabetes risk in observational studies [ 48 ]. Additionally, evidence from experimental, observational and MR studies indicates that high circulating levels of branched-chain amino acids, found in high levels in for example whey protein, increase the risk of type 2 diabetes [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from another study showed that a higher intake of dairy products (e.g., milk, yogurt, cheese and whey protein) was beneficial for glucose regulation and reduced the risk of T2DM (34) . Fan et al (35) showed that consuming 200 g/d of milk reduced the risk of diabetes by 9%. Dairy products have abundant nutrient elements such as protein, minerals and fat (36) .…”
Section: Discussionmentioning
confidence: 99%